Design and Development of Interactive Media in Vocational High Schools Using the Multimedia Development Life Cycle Method Based on Android - Yusuf, Inayatul Izzati Diana; Jahiri, Muhamad; Henderi, Henderi; Ladjamudin, Al-Bahra Bin (PT Mattawang Mediatama Solution, 2024)
This research aims to develop interactive media as a learning medium. Now Indonesia is entering the era of industrial revolution 5.0 which prioritizes technology in all fields, including education. However, unfortunately, learning media, especially in vocational schools, is not sufficient, and teachers must use interactive media to teach students using technology. The method used is the Multimedia Development Life Cycle (MDLC) method with six main stages, namely: Concept, Design, Material Collection, Assembly, Testing and Distribution. From the results of the review, revisions were made according to suggestions from media and material experts. At the Distribution stage, the product was tested on students, the test subjects were class X SMK Yanisba Boarding School Vocational School. Data is collected through surveys. After that, the data is examined, and recommendations are used to update the final product. The aim of this research is to: (1) Create interactive media using Kodular at SMK Yanisba Boarding School (2) Determine the feasibility of interactive media using Kodular at SMK Yanisba Boarding School. Validator assessment of interactive media using Kodular.